Material and immaterial dimensions of clusters. Cooperation and learning as infrastructure for innovation - Michael Steiner; Christian Hartmann (European Regional Science Association (ERSA), 2002)
The paper concentrates on forms of cooperation in a learning context and presents theory-based empirical results of interactive learning processes in different clusters. A general outline of institutional aspects of clusters and networks is given and more specific theories of interactive learning are focussed. An extensive comparison of forms of such learning processes is undertaken, and finally policy conclusions are be drawn.
Keywords: 330